Implementasi Konsep Etika Peserta Didik Menurut KH. Hasyim Asy’ari Dalam Kitab Adabul Alim Wal Muta’alim - Yanti, Yanti Amalia Afifah; Ujang Ruslandi (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study is to find out the concept of student ethics according to KH. Hasyim asy'ari in the book Adabul Alim wal Muta'alim and its implementation at the Al-Hidayah Islamic Boarding School Sukabumi. The type of research used in this study is descriptive research with a qualitative approach by taking the background of the Al-Hidayah Sukabumi Islamic Boarding School. Data collection was carried out by conducting observations, interviews and documentation consisting of the Leadership of the Al-Hidayah Islamic Boarding School, the Ustadz of the Al-Hidayah Islamic Boarding School, and the students of the Al-Hidayah Sukabumi Islamic Boarding School. Analyze the data by giving meaning to the results collected. The results of this study show that: (1) The concept of student ethics according to KH. Hasyim Asy'ari in the book Adabul Alim wal Muta'alim there are four, namely the ethics of students towards themselves, the ethics of students towards their educators, the ethics of students in pursuing knowledge, and the ethics of students towards the book being studied. (2) Implementation of the concept of student ethics according to KH. Hasyim asy'ari at the Al-Hidayah Islamic boarding school in Sukabumi, namely by habituation, coaching and example methods.